Autonomy and Equality Relational Perspectives - Stoljar, Natalie; Voigt, Kristin (Routledge Studies in Contemporary Philosophy, 2022)
philosophy, autonomy, feminist philosophy, political philosophy, ethics, equity, social philosophy